ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI MOTIVASI BELAJAR MATEMATIKA PADA SISWA KELAS VIII D SMP N. 2 CAMPALAGIAN - Rahayu, Ayu; Sahabuddin, Chuduriah; Yusran, Yusran (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2022)
This study is descriptively qualitative and aims to analyze the ability of mathematical communication related to the motivation to study mathematics in class VIII D of SMP Negeri2 Campalagian. Of the 29 students who completed the diagnostic test, 6 showed high levels of mathematical communication skills, 9 showed moderate mathematical communication skills, and 12 showed low levels of mathematical communication skills. rice field. It was reduced from 29 students to 6 students, with talking subjects each covering the mathematical communication skills of low, middle and high level students. In this study, mathematical communication skills tests and interviews were used to obtain the desired results. The results of this study only met 3-4 indicators of mathematical communication, but intermediate level mathematical communication skills, the ability to connect jasmani mathematical ideas, students who failed to meet everyday events. It was the ability of. Express using mathematical symbols when presenting ideas. Achieve high level communication skills, ability to explain math sentences, ideas, everyday situations, math relationships with sentences and photos: Students who meet all the indicators of math communication adjusbility.